Tiryns, Griechenland: Die Arbeiten der Jahre 2012 bis 2014 - Maran, Joseph; Papadimitriou, Alkestis; Hinzen, Klaus-G.; Schultz, Michael; Schmid-Schultz, Tyede H.; Thaler, Ulrich (e-Forschungsberichte des DAI, 2023)
The research results presented here shed new light on various aspects of the Late Mycenaean community of Tiryns between ca. 1250 and 1150 BC. These roughly hundred years were of crucial significance for the site since they brought along the transformation of the palatial center into one of the most important towns of the early post-palatial period in Greece. The report focuses on four sub-projects that are relevant for this period: (1) the study of wallpaintings of the late palace which were uncovered in excavations since the early 20th century, (2) a paleoseismological investigation of whether the site was indeed destroyed around 1200 BC by an earthquake, (3) a physical anthropological and paleopathological study of skeletons of the late palatial and post-palatial periods encountered since the 1960s in the Lower Citadel and (4) the new excavation in the Northwestern Lower Town which tries to understand the unique phenomenon of the seemingly systematic rebuilding of the area to the north of the citadel in the immediate aftermath of the palatial destruction.